Biotransformasi Tartrazin oleh Bakteri Usus Manusia - Batubara, Melvariani Syari; Ginting, Nurmaini (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2018)
The aimed of this research was to investigated human intestinal bacteria (Streptococcus faecalis, Eschericia coli, Salmonella Sp., and Vibrio fischeri), to investigated dose of tartrazine, and to investigated biotransformation of tartrazine by human intestinal bacteria (Streptococcus faecalis, Eschericia coli, Salmonella Sp., and Vibrio fischeri). The method of this research was experiment with significant correlation to investigated biotransformation of tartrazine by human intestinal bacteria (Streptococcus faecalis, Eschericia coli, Salmonella Sp., and Vibrio fischeri). This study is primarily focussed on made bacteria medium, made standart inoculums of bacteria, and evaluation for activity of human intestinal bacteria (Streptococcus faecalis, Eschericia coli, Salmonella Sp., and Vibrio fischeri). The results obtained were attributed to the human intestinal bacteria was used in this research was biotransformated tartrazine. From the results that had been increase dose of tartrazine correlation with increase biotransformation by human intestinal bacteria. Highest dose of tartrazine was 15 mg, and highest biotransformation by Vibrio fischeri, which rate of zone decolourisation diameter was 1,22 cm, and rate of zone decolourisation was 1,44 cm2. Statistically showed significantly in correlation dose of tartrazine with rate of zone decolourisation (0,001 < P < 0,05), but statistically showed non significantly in correlation bacteria with rate of zone decolourisation (0,05 < P < 0,268).